Type I Collagen Cross-Linked C-Terminal Telopeptide as A Predictor Marker of Osteoporosis in Iraqi Thyroid Diseases Patients (Iraqi Journal of Medical Sciences, 2024)
Background: Adult bone strength and shape are physiologically maintained in large part by thyroid hormones. Thus, there exists a correlation between thyroid diseases and bony outcomes.Objective: To assess the level of type I collagen cross-linked C-terminal telopeptide in Iraqi patients with thyroid disorders and its relationship to other biochemical markers.Methods: Eighty Iraqi thyroid disease patients (40 with hypothyroidism and 40 with hyperthyroidism) were included in this study, aged between 30 and 65 years. Patients were chosen from the Baghdad Teaching Hospital in the Medical City Complex. The 40 individuals in the healthy control group (20 males and 20 females) ranged in age from 30 to 55 years.Results: Among the three study groups, there was a highly significant decrease in vitamin D3 in hypothyroidism and hyperthyroidism compared to control. A statistically significant increase in alkaline phosphatase levels was seen among the study groups (hypothyroidism, hyperthyroidism, and control); however, no statistically significant differences were seen between phosphate and calcium levels. There was a highly significant rise in C-terminal telopeptide (CTX-1) between the groups with hypothyroidism and hyperthyroidism and the control group; similarly, the hyperthyroidism group showed a highly significant increase in CTX-1.Conclusion: There was a substantial increase in type I collagen cross-linked C-terminal telopeptide in hypothyroidism and hyperthyroidism compared to control. This rise could be interpreted as a predictive marker of osteoporosis in thyroid disease. Keywords: CTX-1, hypothyroidism, thyroid hormone, type I collagen cross-linked C-terminal telopeptide, osteoporosisCitation: Ghadban AH, Tahir NT, Jawad RS. Type I collagen cross-linked C-terminal telopeptide as a predictor marker of osteoporosis in Iraqi thyroid diseases patients. Iraqi JMS. 2024; 22(2): 330-338. doi: 10.22578/IJMS.22.2.19
Keywords: CTX1; hypothyroidism; thyroid hormone; type I collagen crosslinked Cterminal telopeptide; osteoporosis